"The Extraordinary Powers of the Judicial Control Officer in the Criminal Code of the Saudi Criminal Procedure Law, "Comparative Study of Some Arab Laws - Qatishat, Khadija Abdel Hamid Mustafa (Journal of Economic, Administrative and Legal Sciences, 2017)
The aim of the research is to identify the exceptional powers of the arresting officers in the criminal offense of the Saudi criminal procedure system and the comparative laws by following the comparative analytical descriptive method, the definition of the concept of the known offense and the judicial controls in cases where the conditions of the offense are observed, Of the Disciplinary Officer. The results of the comparison between the provisions of the exceptional authorities in the Saudi system and some comparative Arab laws showed that the Saudi regulator used the term "flagrante" and did not use the term "crime" as the most comparable laws. He did not specify the severity of the crime as one of the most important direct controls of the criminal investigation officer to investigate the case of flagrante delicto, nor did he specify the time period in which the crime would continue in the case of flagrante delicto. The researcher recommended the use of the term "wearing clothes" instead of the "offense" in the Saudi system, and adding a text specifying the criterion for estimating the seriousness of the crime in case of flagellation.